Wheels of the Past: Trams as the Lifeline of Semarang City 1881-1940 - Safitri, Rahma Danisa Eka; Khawismaya, Herlina Putri; Amalia, Qotrunnida; Wijayati, Putri Agus; Pratiwi, Ardela Iga (Siginjai: Jurnal Sejarah, 2025)
Trams played an important role in the development of Semarang City from 1881 to 1940. As a mode of transportation in the city, trams are not only a means of transporting passengers and goods, but also a major driver of economic growth and urban spatial development. This research uses historical methods, including heuristics, source criticism, interpretation, and historiography. The results show that the Semarang-Juana steam tram, operated by Samarang-Joana Stoomtram Maatschappij (SJS), is the backbone of transportation to connect produce production areas with ports, as well as encourage urbanization and economic growth. Trams also form new economic corridors and expand social interaction between community groups. However, trams eventually disappeared due to the development of transportation technology and changes in urban spatial planning.